Intervaginal space injection of a liquid metal can prevent breast cancer invasion and better-sustain concomitant resistance. (30th March 2020) - Cao, Yupeng; Hu, Xiajun; Zhang, Qiang; Hua, Wenda; Hu, Nan; Nie, Yifeng; Xu, Xue; Xu, Yonggang; Yang, Chongqing; Zhou, Xiaohan; Liu, Wentao; Han, Dong
Abstract : CW invasion by the primary tumor was inhibited by ISI of an LM. DCs were activated by the LM to sustain CR. Abstract : Chest wall (CW) invasion by recurrent or locally advanced breast cancer (BC) requires further treatment with more potential complications. The negative margin of a tumor has been proposed as a critical factor in BC surgery; however, the ideal margin remains controversial, and data suggest that this parameter cannot further reduce CW invasion. Herein, a liquid metal (LM) was introduced as an interstitial stream (IS) to separate the BC and CW to prevent tumor invasion into the CW. Successful continuous separation and the prevention of CW invasion were observed in 4T1 tumor-bearing mice by magnetic resonance imaging (MRI) and anatomical observation, respectively. Furthermore, the inhibition of primary tumor growth and the prevention of accelerated secondary tumor growth suggest that this method potently retains concomitant resistance (CR). Subsequently, the enhanced maturation of dendritic cells (DCs) from the LM group suggests that this method may activate T cell-dependent immunity to retain CR through DC maturation. Additionally, LM was shown to have limited toxicity. In this study, LM was introduced as an IS into the interstitial space, which potentially links superficial and deep sites in the body, and showed excellent ability to prevent CW invasion, thus also providing a potential way to efficiently deliver drugs.